GEOREFERENZIAZIONE ACCURATA, VELOCE E GRATUITA - Cantoro, Gianluca (Archeomatica, 2012)
La georeferenziazione di una immagine satellitare o di una fotografia aerea rispetto a un sistema di coordinate di riferimento risulta un processo spesso indispensabile per la comprensione del palinsesto archeologico. Al tempo stesso essa richiede tempi lunghi (a volte ore) e grande accuratezza. Un aiuto perridurre i tempi di individuazione e selezione di corrispondenze fra immagini da georeferenziare e sistema di destinazione, aumentando la precisione a livello sub-pixel, viene oggi offerto da un nuovo set di strumenti gratuiti: AutoGR-Toolkit. Geo-reference of Images with AutoGR-Toolkit AutoGR-Toolkit is a set of Pythonscripts converted to ".EXE” files with py2exe v0.6.9. The purpose of thetoolkit is to facilitate and speedup the process of geo-referencing images withfree and open source tools and graphical user-friendly interfaces. It embeds 4scripts (GGRAB, AuttoGR-Sift, GeoRef Filtering, GeoTiff Converter) and 2 algorithmlibraries (ASift and GDAL) to assist the user in geo-referencing oneimage on another according to the specifi c geographical projection. The use ofthe software does not require any special skill and allows the user to go frominput to output in few minutes, still keeping the possibility to customize almost every parameter to improve the fi nal accuracy. This paper describes the basic principles and functionalities behind every tool in the Toolkit. AutoGR-Toolkit is freely available at the URL http://www.ims.forth.gr/AutoGR.